X = y
y = 4
By the substitution property, we can replace y with 4 in that first equation.
x = 4
Factor by grouping. Group up the terms into pairs, factor each pair, then factor out the overall GCF.
x^3 + 2x^2 - 16x - 32
(x^3 + 2x^2) + (-16x-32) ... pair up terms
x^2(x + 2) + (-16x - 32) ... factor x^2 from the first group
x^2(x + 2) - 16(x + 2) ... factor -16 from the second group
(x^2 - 16)(x + 2) .... factor out (x+2)
(x - 4)(x + 4)(x + 2) .... Use the difference of squares to factor x^2-16
---------------------------
The original expression completely factors to (x - 4)(x + 4)(x + 2)
The three factors are x - 4 and x + 4 and x + 2
Step-by-step explanation:
the angle CDB is the supplementary angle to 9x+10 (angle ADC).
that means they stand together for 180°. as all angles around a single point on one side of a line are together always 180°.
and then, the sum of all angles in a triangle is always 180°.
so,
CDB + (4x + 10) + 50 = 180
CDB = 180 - (9x + 10) = 180 - 9x - 19 = 170 - 9x
therefore,
(170 - 9x) + (4x + 10) + 50 = 180
170 - 9x + 4x + 10 + 50 = 180
-5x = -50
5x = 50
x = 10
angle CDB = 170 - 9x = 170 - 90 = 80°
<u>Answer</u>
-4x - 2
<u>Explanation</u>
To get the function needed, first calculate the slope of the graph.
slope = (change in y) / (change in x)
= (2 - -2)/(-1 - 0)
= 4/-1
= -4
Now use one of the point (-1, 2) in the graph and a general point (x,y) to find the function.
-4 = (y - 2)/(x - -1)
-4(x + 1) = y - 2
-4x - 4 = y - 2
y = -4x - 4 + 2
= -4x - 2
∴ f(x) = -4x - 2